STRATEGI KOMUNIKASI PEMASARAN UMKM BANGJERI DALAM MENGHADAPI PANDEMI COVID-19 - Muhammad Faiz Athallah; Indria Angga Dianita (Journal of Management Small and Medium Enterprises (SMEs), 2022)
This study aims to find out the strategies of marketing communication used by Bangjeri SMEs in adapting to the COVID-19 pandemic. The research method is descriptive qualitative with an interpretive paradigm. Data was collected from interviews, documentation, and literature studies, conducted the data validity using source triangulation techniques. The results showed that the Bangjeri MSME message strategy has not designed the communication goals and it uses a creative forms of rational and emotional messages. In the media strategy, Bangjeri SMEs uses direct communication channels and indirect communication channels such as Instagram and WhatsApp. Bangjeri SMEs are also taking advantage of the gaps in the social life of consumers caused by the COVID-19 pandemic. Keywords: Marketing Communication, Marketing Communication Strategy, SMEs, COVID-19 Pandemic